Varieties of collaboration in public service delivery. Issue 4 (2nd October 2018) - Kekez, Anka; Howlett, Michael; Ramesh, M.
Abstract: Collaboration – and its cognates consultative in-house service delivery, contracting out, commissioning, co-management, co-production, and third party certification – have in recent years been at the center of efforts to reform the public sector and devolve its capacity for policy implementation and service delivery. While the arguments in support of the use of different types of collaborative service delivery are plausible and the intentions motivating them laudable, the crucial questions to ask are: what kind of service delivery arrangement is "collaborative?" And, when could such an arrangement be used? Seeking answers to posed questions this article, and articles in the special issue it introduces, conceptualize and explore alternative arrangements in public service delivery by investigating them though governance lenses. After addressing the nature and collaborative potential for each type of service delivery, the article situates them in the model of capacity combining analytical, managerial, and political competences over three levels of governance activities. It shows that while the success of all collaborative arrangements for public service delivery is linked to political capacities, each arrangement involves a critical type of managerial or analytical capacity which serves as its principle vulnerability. The extent to which various collaborative arrangements can address these vulnerabilities is assessed along with their design requisites and potential utility.